Dialogue of life and its significance in inter-religious relation in Malaysia - Suraya Sintang; Azizan Baharuddin; Khadijah Mohd Khambali @ Hambali (International Society of Muslim Philosophers and Theologians, 2012)
Dialogue of life is a form of inter-religious dialogue which commonly takes place at any place and any time. It is a dialogical relation to promote amicable relation with people from different religions. It begins when one encounters, lives and interacts with the others and participates in daily life activities together. It is a social interaction which shows the involvement of non-elite participants in the inter-religious dialogue at the grass roots level. The non-elite participation in the inter-religious dialogue is necessary to accommodate the challenge of pluralistic society. This kind of process which involves the social interaction in everyday activity is known as a dialogue of life. Those activities can be seen in the life experience of living together with mix-faith family, celebrating festivities and wedding ceremony as well as doing (running) business with the other religious communities. The aim of this paper is to elucidate the concept of dialogue of life and how this dialogue has a significant impact on encouraging positive interaction among people of different religions in Malaysia.